The Use of a Wearable Camera, SenseCam, as a Pictorial Diary to Improve Autobiographical Memory in a Patient with Limbic Encephalitis: A Preliminary Report - Berry, Emma; Kapur, Narinder; Williams, Lyndsay; Hodges, Steve; Watson, Peter; Smyth, Gavin; Srinivasan, James; Smith, Reg; Wilson, Barbara; Woodberry, Ken (Neuropsychological Rehabilitation, 2007)
This case study describes the use of a wearable camera, SenseCam, which automatically captures several hundred images per day, to aid autobiographical memory in a patient, Mrs B, with severe memory impairment following limbic encephalitis. By using SenseCam to record personally experienced events we intended that SenseCam pictures would form a pictorial diary to cue and consolidate autobiographical memories. After wearing SenseCam, Mrs B plugged the camera into a PC which uploaded the recorded images and allowed them to be viewed at speed, like watching a movie. In the control condition, a written diary was used to record and remind her of autobiographical events. After viewing SenseCam images, Mrs B was able to recall approximately 80% of recent, personally experienced events. Retention of events was maintained in the long-term, 11 months afterwards, and without viewing SenseCam images for three months. After using the written diary, Mrs B was able to remember around 49% of an event; after one month with no diary readings she had no recall of the same events. We suggest that factors relating to rehearsal/re-consolidation may have enabled SenseCam images to improve Mrs B’s autobiographical recollection.